Pathophysiology of Trans-Synaptic Adhesion Molecules: Implications for Epilepsy - Gorlewicz, Adam; Kaczmarek, Leszek (Frontiers in Cell and Developmental Biology, 2018)
Chemical synapses are specialized interfaces between neurons in the brain that transmit and modulate information, thereby integrating cells into multiplicity of interacting neural circuits. Cell adhesion molecules might form trans-synaptic complexes that are crucial for the appropriate identification of synaptic partners and further for the establishment, properties, and dynamics of synapses. When affected, trans-synaptic adhesion mechanisms play a role in synaptopathies in a variety of neuropsychiatric disorders including epilepsy. This review recapitulates current understanding of trans-synaptic interactions in pathophysiology of inter-neuronal connections. In particular, we discuss here the possible implications of trans-synaptic adhesion dysfunction for epilepsy.